2017
DOI: 10.1126/scisignal.aam5345
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor C/EBPβ in the dorsal root ganglion contributes to peripheral nerve trauma–induced nociceptive hypersensitivity

Abstract: The transcription factor C/EBPβ may be a master regulator of neuropathic pain caused by peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
(130 reference statements)
9
48
0
Order By: Relevance
“…These nociceptive hypersensitivities occurred 4 weeks post-microinjection and persisted for at least 8 weeks (Fig. 5d-g), consistent with the 3-4-week lag period of AAV5 expression, which lasts for at least 3 months [27,30,31]. Neither virus affected locomotor function (Table 2) or basal contralateral paw withdrawal responses (Fig.…”
Section: Drg Overexpression Of Creb Leads To Nociceptive Hypersensitivitysupporting
confidence: 76%
See 2 more Smart Citations
“…These nociceptive hypersensitivities occurred 4 weeks post-microinjection and persisted for at least 8 weeks (Fig. 5d-g), consistent with the 3-4-week lag period of AAV5 expression, which lasts for at least 3 months [27,30,31]. Neither virus affected locomotor function (Table 2) or basal contralateral paw withdrawal responses (Fig.…”
Section: Drg Overexpression Of Creb Leads To Nociceptive Hypersensitivitysupporting
confidence: 76%
“…In the present study, we for the first time showed the CREB is widely expressed throughout the brain, spinal cord, and DRG [36]. Like other transcription factors such as myeloid zinc finger 1, CCAAT/enhancer binding protein β, and OCT1 [28][29][30]32], CREB may be upregulated in painprocessing regions under neuropathic pain conditions. The expression of p-CREB in the DRG and spinal cord dorsal horn neurons was significantly increased in a rat model of type II diabetic neuropathic pain [15].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The present study demonstrated that SNL persistently enhanced the C/EBPβ protein level in the ipsilateral L4 DRG, rather than the intact/adjacent L3 DRG, ipsilateral and contralateral L4 DRGs. Based on these results, such increase only occurs in the damaged DRG neurons, as C/EBPβmRNA was identi ed in small, medium, and large DRG neurons, rather than satellite glial cells, of naive mice [24]. In addition, in the CCI mouse model, in the ipsilateral L3/4 DRGs, many neurons labeled with C/EBPβmRNA were positive for ATF3, the injury marker [24].…”
Section: Discussionmentioning
confidence: 92%
“…A previous study revealed that chronic sciatic nerve construction injury upregulated C/EBPβexpression at protein and mRNA levels in ipsilateral L3/4 DRGs [24]. However, whether C/EBPβ expression in intact/adjoining DRG was altered following peripheral nerve trauma is unclear.…”
Section: Discussionmentioning
confidence: 97%